PENGABDIAN KEPADA MASYARAKAT MESIN PENGGILING KEDELAI UNTUK PRODUKSI SUSU KEDELAI PADA INDUSTRI RUMAH TANGGA - masdani masdani; Zaldy Kurniawan; Hasdiansah Hasdiansah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Community service activities( PKM) carried out in collaboration with soy milk business partners in Parit Padang Village, Sungailiat District, Bangka Regency, Bangka Belitung Islands Province. The production process carried out by partners still uses manual methods with simple equipment so that to make soya milk in the amount of 3 kilogram takes approximately 30- 60 minutes. The purpose of this activity is to assist partners in increasing the productivity of soya milk businesses. Through this (PKM) activity, it is expected to improve the performance of partners in soya milk production. This (PKM) activity is carried out through several stages, namely: survey of partner problems, procurement of soybean grinding machines, and brief training on machine operation and maintenance. This program runs well and smoothly with training and assistance to partners. After this activity, partners get appropriate technology in the form of machines and maintenance services if the machine experiences problems or damages and there is an increase in the quality and quantity of soya milk production with an increase in production capacity of 6 kilogram per hour.